Nilai pendidikan Kristiani "terimalah satu akan yang lain" dalam bingkai moderasi beragama - Rinto Hasiholan Hutapea (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
This study specifically examined the interaction of IAKN Palangka Raya Christian students in a joint group of Real Work Lectures with IAIN Palangka Raya Islamic students and Hindu students kaharingan IAHN Palangka Raya. The location of special activities of Bukit Sua Village and Mungku Baru Village. The purpose of this study is also to examine and analyze the implementation of the value of Christian education "accept one another" Romans 15:7 in the framework of religious moderation. Empirical studies become the methods that researchers use to achieve these goals. The results stated that the interaction and implementation of the value of Christian education "accept one another" in the framework of religious moderation by Christian students in a combined group with Islamic students and Hindu Kaharingan students was empirically realized very well. Christian students amid differences in faith in KKN activities can realize and apply the values of Christian education and religious moderation with indicators: attitude of acceptance with love, communication based on love, cooperation based on love, attitudes that make room for differences in beliefs, and attitudes that accept local culture as part of religious expression. AbstrakPenelitian ini khusus mengkaji interaksi mahasiswa Kristen IAKN Palangka Raya dalam kelompok gabungan Kuliah Kerja Nyata dengan mahasiswa Islam IAIN Palangka Raya dan mahasiswa Hindu Kaharingan IAHN Palangka Raya. Lokasi kegiatan khusus Kelurahan Bukit Sua dan Kelurahan Mungku Baru. Tujuan penelitian ini juga untuk mengkaji dan menganalisis implementasi nilai pendidikan Kristiani "terimalah satu akan yang lain" melalui pembacaan Roma 15:7 dalam bingkai moderasi beragama. Studi empiris menjadi metode yang peneliti gunakan untuk mencapai tujuan tersebut. Hasil penelitian menyatakan bahwa interaksi dan implementasi nilai pendidikan kristiani ??Sterimalah satu akan yang lain? dalam bingkai moderasi beragama oleh mahasiswa Kristen dalam kelompok gabungan dengan mahasiswa Islam dan mahasiswa Hindu Kaharingan secara empiris terwujud dengan sangat baik. Mahasiswa Kristen di tengah-tengah perbedaan keyakinan, dalam dalam kegiatan KKN, dapat mewujudkan dan menerapkan nilai pendidikan kristiani dan moderasi beragama dengan indikator: sikap menerima dengan kasih, komunikasi berlandaskan kasih, bekerja sama didasarkan pada kasih, sikap yang memberi ruang terhadap perbedaan keyakinan, serta sikap yang menerima budaya lokal sebagai bagian dari ekspresi beragama.